Designing of an Efficient Whole-Cell Biocatalyst System for Converting L-Lysine Into Cis-3-Hydroxypipecolic Acid - Hu, Shewei; Li, Yangyang; Zhang, Alei; Li, Hui; Chen, Kequan; Ouyang, Pingkai (Frontiers in Microbiology, 2022)
Cis-3-hydroxypipecolic acid (cis-3-HyPip), a key structural component of tetrapeptide antibiotic GE81112, which has attracted substantial attention for its broad antimicrobial properties and unique ability to inhibit bacterial translation initiation. In this study, a combined strategy to increase the productivity of cis-3-HyPip was investigated. First, combinatorial optimization of the ribosomal binding site (RBS) sequence was performed to tune the gene expression translation rates of the pathway enzymes. Next, in order to reduce the addition of the co-substrate α-ketoglutarate (2-OG), the major engineering strategy was to reconstitute the tricarboxylic acid (TCA) cycle of Escherichia coli to force the metabolic flux to go through GetF catalyzed reaction for 2-OG to succinate conversion, a series of engineered strains were constructed by the deletion of the relevant genes. In addition, the metabolic flux (gltA and icd) was improved and glucose concentrations were optimized to enhance the supply and catalytic efficiency of continuous 2-OG supply powered by glucose. Finally, under optimal conditions, the cis-3-HyPip titer of the best strain catalysis reached 33 mM, which was remarkably higher than previously reported.